PERSEPSI DAN PEMAHAMAN MASYARAKAT KABUPATEN KARAWANG TERHADAP PERNIKAHAN BEDA AGAMA DAN AKIBATNYA - Ika Nurjanah; Oyoh Bariah; Acep Nurlaeli; Sayan Suryana (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
This research is motivated by the large number of Indonesian people who carry out interfaith marriages (Muslims with non-Muslims) this is evidenced by the presence of 24,677 couples who married different faiths in 1980, then in 1990 there were 26,688 couples, while the latest data in 2000 were 2,673 couple. Although the nominal number of interfaith marriages has decreased since 1980-2000, the number of around 2673 couples is still relatively high. In fact, Islam and Indonesian laws strictly prohibit it. The method used in this study is a qualitative method, which is a research procedure that produces descriptive data in the form of written or spoken words from people and behavior and can be observed from the facts that exist today. The results of the research obtained are: all people agree that the law of interfaith marriage is unlawful and the marriage is not valid because it violates Islamic law and Indonesian law Not a few people (respondents) argue that the causative factors for interfaith marriage problems are lust, wealth, throne and lack of religious education, so it doesn't matter if you have a partner of a different religion even to the level of marriage.